2007
DOI: 10.1021/tx700137a
|View full text |Cite
|
Sign up to set email alerts
|

3,3′-Diselenodipropionic Acid, an Efficient Peroxyl Radical Scavenger and a GPx Mimic, Protects Erythrocytes (RBCs) from AAPH-Induced Hemolysis

Abstract: 3,3'-diselenodipropionic acid (DSePA), a derivative of selenocystine, has been synthesized and examined for antioxidant activity, glutathione peroxidase (GPx) activity, and cytotoxicity. The effect of DSePA on membrane lipid peroxidation, release of hemoglobin, and intracellular K+ ion as a consequence of erythrocyte (red blood cells or RBCs) oxidation by free radicals generated by 2,2'-azobis(2-amidinopropane) hydrochloride (AAPH) were used to evaluate the antioxidant ability. Lipid peroxidation, hemolysis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 37 publications
2
61
0
Order By: Relevance
“…This was in accordance with our earlier studies, where it has been suggested that hemoglobin molecule being bigger in size is difficult to be released from the damaged membranes, while K + ions, being smaller in size, can be leaked even with slight disturbance in the membrane structure [27]. Since the anti-hemolytic ability of selenium compounds may be influenced by the presence of thiols, estimation of GSH levels was carried out in these samples.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…This was in accordance with our earlier studies, where it has been suggested that hemoglobin molecule being bigger in size is difficult to be released from the damaged membranes, while K + ions, being smaller in size, can be leaked even with slight disturbance in the membrane structure [27]. Since the anti-hemolytic ability of selenium compounds may be influenced by the presence of thiols, estimation of GSH levels was carried out in these samples.…”
Section: Resultssupporting
confidence: 90%
“…When compared with inorganic selenium compounds like Na 2 SeO 3 , these compounds exhibit better anti-hemolytic activity. Considering the fact from our previous studies [27] that Na 2 SeO 3 although known to exhibit better GPx activity is more toxic than any of these compounds, the present studies with organoselenium compounds gain significance.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Hemolysis of RBCs is a very good model for studying free radical induced oxidative damage to membranes and to evaluate the antioxidant activity of compounds [38,39]. Erythrocytes are known as main targets of oxidative stress due to the presenting of membrane polyunsaturated fatty acids the linolenic and arachidonic acids [40].…”
Section: Antihemolytic Activitymentioning
confidence: 99%